Acknowledgment to Reviewers of Scientia Pharmaceutica in 2020 - Scientia Pharmaceutica Editorial Office (MDPI AG, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Scientia Pharmaceutica maintains its standards for the high quality of its published papers [...]